Sexual Reproduction Counseling Education Strategies to Increase Adolescent Awareness: (Case Study of Adolescents in Kampung Baru Hamlet, Sidomukti Village) - Shava Yuliarsih; Siti Muafanah; Latifun Naufa; Ulin Nihayah (Universitas Palangka Raya, 2024)
This study discusses sexual reproductive health education strategies aimed at increasing adolescent awareness in Kampung Baru Hamlet, Sidomukti Village, Indonesia. It identifies key challenges, including limited knowledge, social taboos, and ineffective educational approaches related to reproductive health. The authors recommend interactive and participatory educational methods that actively involve adolescents in the learning process, making the content more relevant and easier to understand. The use of digital media and technology is also emphasized as an effective means to reach and engage young people. In addition, collaboration between parents, teachers, and health professionals, along with supportive government policies, is essential to create an environment conducive to reproductive health education. The main goal of this study is to empower adolescents to make informed and responsible decisions regarding their sexual health.